The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1159/000277632
|View full text |Cite
|
Sign up to set email alerts
|

IL-6, IL-8 and IL-10 Levels in Healthy Weight and Overweight Children

Abstract: Background/Aim: In adults, studies have shown that obesity is a chronic low-grade inflammatory state characterized by altered levels of cytokines. Studies in children have mainly focused on C-reactive protein and adiponectin, and there is limited data for other inflammatory markers in healthy weight and overweight children. The aim of this study was to measure IL-6, IL-8 and IL-10 levels in healthy normal weight and overweight children at 8 and 15 years. Methods: 118 normal weight and overweight children (59 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 95 publications
6
53
1
5
Order By: Relevance
“…(3). This hypothesis has partially been proven by a longitudinal study of 118 healthy children, which found raised IL6 levels in 15-year-old overweight/obese girls with no difference at the age of 8 years (34). In our prepubertal group, the concentrations of all investigated inflammatory markers did not show significant gender differences and thus confirmed other international reports in children (15,18,25).…”
Section: Discussionsupporting
confidence: 91%
“…(3). This hypothesis has partially been proven by a longitudinal study of 118 healthy children, which found raised IL6 levels in 15-year-old overweight/obese girls with no difference at the age of 8 years (34). In our prepubertal group, the concentrations of all investigated inflammatory markers did not show significant gender differences and thus confirmed other international reports in children (15,18,25).…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, subtle differences in inflammatory mediators may also have been missed due to the relatively small groups with a wide age-range. For example, we were unable to confirm the increased IL-10 levels previously observed in obese adolescent girls [18]. Moreover, based on previous studies [43], we would also have expected lower adiponectin levels in obese children than in controls, but merely observed a trend (p00.09).…”
Section: Discussioncontrasting
confidence: 65%
“…Earlier studies on small sets of circulating mediators showed greater levels of inflammatory mediators, including high-sensitivity C-reactive protein (hsCRP), leptin, IL-6 and IL-8, together with decreased levels of the insulin-sensitising adipokine, adiponectin, and higher leucocyte numbers in obese children than in lean controls [15][16][17][18]. These studies indicated that low-grade systemic inflammation is already present during childhood obesity.…”
Section: Introductionmentioning
confidence: 90%
“…Other inflammatory markers, such as IL-1α, IL-2, IL-4, IL-8, IL-10, vascular endothelial growth factor (VEGF), interferon-γ (IFN-γ), monocyte chemoattractant protein-1 (MCP-1), and epidermal growth factor have been less investigated [7,12]. Glowinska and Urban [13] did not find differences in IL-8, IL-10, and MCP-1 levels between 14- to 17-year-old obese and normal-weight adolescents.…”
Section: Introductionmentioning
confidence: 99%